Rethinking Biovilla’s human resources structure - González, Cecilia González (2022)
Biovilla is a sustainable cooperative tha tfocuses on regenerative and sustainable development. Due to its recent and rapid growth, it is apparent that Biovilla’s human resource structure is insufficient to meet the new daily demands. This project aims to assess the current situation of Biovilla’s human resources and identify the core problems of current practices that may prevent the organisation from leveraging its potential growth. Recommendations are there for e made to improve current human resource practices in order to enhance the organisation's performance. These include creating job descriptions, an organigramand recommendations on leadership, recruitment, on boarding, internal communication and performance evaluation strategy. To define these recommendations, data on Biovilla's internal and external environment was collected and then analysed and interpreted using thematic pattern analysis for better contextualisation.